Factors Affecting the Compliance of MSME Entrepreneurs as Individual Taxpayers - Rahmawati, Septia; Noor, Aspyan (Fakultas Ekonomi dan Bisnis Universitas Mulawarman, 2024)
This study aims to research and analyze the influence of taxpayer awareness, tax knowledge and understanding, tax incentives, and tax sanctions on the compliance of Individual Taxpayers. This study uses Purposive sampling where the selection is selected through certain criteria. The number of this research is as many as 100 MSME respondents registered at KPP Pratama Samarinda Ulu. This study is quantitative in data collection with questionnaires, namely testing the independent variables of taxpayer awareness, tax knowledge and understanding, tax incentives, and tax sanctions on variables bound by individual taxpayer compliance. This analysis uses a multiple linear regression analysis technique processed through SPSS version 26. The results of this study show that the variables of taxpayer awareness, tax knowledge and understanding, tax incentives and tax sanctions do not have a significant influence on the compliance of individual MSME taxpayers registered at KPP Pratama Samarinda Ulu